Human medical research : Ethical, legal and socio-cultural aspects - Schildmann, Jan (Springer Basel, 2012)
Medical research involving human subjects has contributed to considerable advancements in our knowledge, and to medical benefits. At the same time the development of new technologies as well as further globalisation of medical research raises questions that require the attention of researchers from a range of disciplines. This book gathers the contributions of researchers from nine different countries, who analyse recent developments in medical research from ethical, historical, legal and socio-cultural perspectives. In addition to reflections on innovations in science such as genetic databases and the concept of "targeted therapy" the book also includes analyses regarding the ethico-legal regulation of new technologies such as human tissue banking or the handling of genetic information potentially relevant for participants in medical research. Country and culture-specific aspects that are relevant to human medical research from a global perspective also play a part. The value of multi- and interdisciplinary analysis that includes the perspectives of scholars from normative and empirical disciplines is a shared premise of each contribution.